Midterm results after St Jude Medical Epic porcine xenograft for aortic, mitral, and double valve replacement. Issue 8 (29th June 2020) - Jawad, Khalil; Lehmann, Sven; Koziarz, Alex; Dieterlen, Maja; Feder, Stefan; Misfeld, Martin; Garbade, Jens; Rao, Vivek; Borger, Michael
Abstract: Background: The aim of this study was to evaluate the results after stented porcine xenograft implantation (Epic, SJM, St Paul, MN) with Linx anticalcification treatment in elderly patients at our high‐volume tertiary care center. Methods: A total of 3825 patients undergoing aortic (AVR = 2441), mitral (MVR = 892), or double valve (DVR = 492) replacement between 11/2001 and 12/2017 with Epic xenografts were evaluated. Outcomes were assessed by reviewing the prospectively acquired hospital database results, and regular annual follow‐up information was acquired from questionnaires or telephone interviews. Results: For patients undergoing AVR, MVR, DVR, age at surgery were 76.4 ± 6, 71.2 ± 9, 72.9 ± 8 years; active endocarditis was an indication for valve surgery in 4.5%, 20.7%, 19.7%; and the predicted median (interquartile range [IQR]) mortality risk (EuroSCORE II) was 5.2% (3.1%‐9.4%), 7.5% (3.9%‐16.2%), 9.9% (6.0%‐19.6%), respectively. Median follow‐up was 3.04 (IQR: 0.18‐5.21). Thirty‐day survival was 91.2% ± 0.6%, 87.6% ± 0.1.1%, 84.7% ± 1.6%; and 10‐year survival was 56.7% ± 1.0%, 59.4% ± 2.5%, 50.45% ± 3.1%, respectively. Patients who underwent MVR versus AVR were at significant increased risk for reoperation for endocarditis (adjusted odds ratio; 2.2, 95% confidence interval; 1.29‐3.7; P  = .003). There was no significant difference in all‐cause mortality at midterm in AVR vs MVR in the matched cohort ( P  = .85). Conclusions: Implantation of the Epic stented porcine xenograft is associated with acceptable survival and freedom from valve‐related complications or reoperation due to structural valve disease at midterm follow‐up.